Integrating business model for sustainability and performance management to promote occupational health and safety—A discussion of value - Johanson, Ulf; Aboagye, Emmanuel; Yao, Jun (Frontiers in Sustainability, 2022)
The concept of business model has been around in scientific discussions for over half a century, but the adoption of business model for sustainability is much more recent. What constitutes a business model for sustainability is far from clear, and what drives the business model for sustainability to success needs further elaboration. The current paper adopts a conceptual approach to clarify the components of the business model for sustainability, focusing on the discussion of value addressed in its concept, and the interplay between the business model for sustainability and the internal performance management system. Furthermore, we connect our discussion to occupational health and safety because employee health and safety, one of the important elements of human capital, have been regarded as critical to the sustainable development of companies and society. We argue that OHS should be a fundamental cornerstone in doing business and should not be viewed as an afterthought of production and financial concerns. Therefore, OHS and employee relations should be addressed within the business model. The more important issue is the alignment of the value propositions, value creation, and value capture that underpin both the business model for sustainability and the internal performance management system. If the performance management system is decoupled from the business model, the long-term and short-term occupational health and safety advantages and the sustainable value propositions to stakeholders will not be realized.